Macular Vessel Density Changes in Young Adults With High Myopia: A Longitudinal Study - Shi, Ya; Ye, Luyao; Chen, Qiuying; Hu, Guangyi; Yin, Yao; Fan, Ying; Zhu, Jianfeng; He, Jiangnan; Zheng, Zhi; Zou, Haidong; Xu, Xun (Frontiers in Medicine, 2021)
Background: To characterize the longitudinal change of macular vessel density in young adults and its associated factors. Methods: The right eyes of 309 participants (75 high myopic, 194 mild-to-moderate myopic, and 40 healthy) were followed up for twenty-one months. OCTA images were acquired at two visits using follow-up scans. Macular vessel density was calculated globally and in the nine early treatment diabetic retinopathy study (ETDRS) subfields of the macula superficial layer. Results: The macular vessel density significantly decreased in young myopes after a 21-month follow up (p < 0.05), with variations among sectors. Compared with healthy eyes, HM group exhibited a faster reduction in global macular vessel density (p = 0.0307) as well as in sectors of inner-inferior (II), inner-temporal (IT), and outer-temporal (OT) (all p < 0.05). Multivariate regression analysis showed that longer baseline axial length (AL) was significantly associated with larger reduction of macular vessel density in the inner-inferior, inner-temporal and outer-temporal sectors (all p < 0.05). Conclusions: Compared with emmetropes, high myopes presented greater loss of macular vessel density over time in global and in the inner-inferior, inner-temporal and outer-temporal sectors. A longer baseline AL was associated with larger changes of macular vessel density in the inner-inferior, inner-temporal and outer-temporal sectors.